2019
DOI: 10.1016/j.jneuroim.2019.577049
|View full text |Cite
|
Sign up to set email alerts
|

Myricitrin blocks activation of NF-κB and MAPK signaling pathways to protect nigrostriatum neuron in LPS-stimulated mice

Abstract: Myricitrin, a bioactive and natural flavonoids, is well known for its anti-inflammatory and antioxidant properties. However, the anti-neuroinflammation and possible mechanism has not been fully elucidated. Therefore, the present study was to investigate the possible mechanism of its neuroprotection and anti-neuroinflammation in the nigrostriatum of LPS-stimulated mice. The results showed that myricitrin improved neuron injury and raised the expressions of PSD-95 protein and TH protein in the nigrostriatum of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Myr treatment can reverse these effects. A previous study showed that Myr inhibited the HMGB1, TLR4, and MyD88 expressions in the neurons, and it restored neuronal damage and in ammation caused by activation of NF-κB and MAPK signal pathways [28]. In this study, up-regulation of lncRNA GAS5 and down-regulation of miR-29a-3p led to a decrease of cell apoptosis, in ammation, and EndMT, as well as reduction of activity of TLR4/NF-κB signaling pathway.…”
Section: Discussionsupporting
confidence: 64%
“…Myr treatment can reverse these effects. A previous study showed that Myr inhibited the HMGB1, TLR4, and MyD88 expressions in the neurons, and it restored neuronal damage and in ammation caused by activation of NF-κB and MAPK signal pathways [28]. In this study, up-regulation of lncRNA GAS5 and down-regulation of miR-29a-3p led to a decrease of cell apoptosis, in ammation, and EndMT, as well as reduction of activity of TLR4/NF-κB signaling pathway.…”
Section: Discussionsupporting
confidence: 64%
“…The results presented by Domitrovic et al [73] suggest that the anti-inflammatory and antioxidant effects of myricitrin (10) are responsible for its hepatoprotective activity. In fact, all the myricitrin (10) in vivo studies presented in Table 2 strongly indicate that 10 exerts its protective effects through the blockage of inflammation, oxidative stress, and apoptosis [44,45,73,74], which confirms myricitrin (10) as a potential candidate for the treatment and prevention of a wide array of disorders related to oxidative stress and inflammation.…”
Section: Zebrafish 1 µMmentioning
confidence: 76%
“…In addition, myricitrin (10) decreased the production of pro-inflammatory factors including IL-1β, IL-6, and TNFα, decreased the level of chemokine MCP-1, and suppressed the expressions of COX-2 and iNOS (Table 2). Meanwhile, myricitrin suppressed HMGB1, TLR4, and MyD88 expression in the nigrostriatum of LPS-stimulated mice, and inhibited NF-κB and mitogen-activated protein kinase (MAPK) signaling pathways activated by LPS [74]. These effects show that myricitrin (10) is efficient in protecting the brain against inflammation and all the nefarious effects it causes.…”
Section: Zebrafish 1 µMmentioning
confidence: 95%
See 2 more Smart Citations